2018
DOI: 10.1119/1.5025289
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and Final Exam Performance in Introductory Physics

Abstract: Most physics instructors believe that adequate sleep is important in order for students to perform well on problem solving, and many instructors advise students to get plenty of sleep the night before an exam. After years of giving such advice to students at Loyola Marymount University (LMU), one of us decided to find out how many hours students actually do sleep the night before an exam, and how that would relate to their performance. The effect of inadequate sleep on exam performance was explored in a second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…For example, in the current study, students who were enrolled in STEM majors reported significantly shorter sleep durations, despite entering college with higher academic indices. This finding converges with reports of late bedtimes and short sleep patterns in students enrolled in physics [ 66 ], biology [ 67 ], and chemistry [ 68 ] collegiate courses. Additional work is needed to understand if these associations reflect the demands and difficulty of STEM coursework, the psychosocial characteristics of STEM majors, or both.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…For example, in the current study, students who were enrolled in STEM majors reported significantly shorter sleep durations, despite entering college with higher academic indices. This finding converges with reports of late bedtimes and short sleep patterns in students enrolled in physics [ 66 ], biology [ 67 ], and chemistry [ 68 ] collegiate courses. Additional work is needed to understand if these associations reflect the demands and difficulty of STEM coursework, the psychosocial characteristics of STEM majors, or both.…”
Section: Discussionsupporting
confidence: 89%
“…A second goal of the study was to test whether sleep disparities were explained by financial burden [ 61 ], feelings of belonging [ 29 ], stress [ 62 ], student athlete status [ 63 ], age [ 64 ], off-campus living [ 65 ], or major (STEM discipline) [ 66–68 ]. The third goal of the study was to investigate whether sleep patterns reflected students’ past performance/ability (high school academic index) versus predicted future academic performance (GPA during the first two semesters of college).…”
Section: Introductionmentioning
confidence: 99%
“…Земля создает гравитационное поле в космосе. Когда масса помещается вблизи Земли, гравитационное поле Земли воздействует на массу, и масса испытывает силу» [9].…”
Section: Introductionunclassified